Elevated monocyte phosphorylated p38 in nearby employees after a chemical explosion - Sulen, André (Sci Rep, 2016)
Personalised health surveillance is infrequent or absent in occupational and environmental medicine. The shortage of functional tests in relevant cells and tissues greatly limits our understanding of environmental exposures and associated disease risk. We evaluated single cell signalling in peripheral blood mononuclear cells from 301 individuals in a cross sectional health survey 18 months after a chemical explosion of sulphorous coker gasoline. The accident created a malodourous environment leading to long-term health complaints. Multiple regression analysis revealed T-cell specific elevated phosphorylation of the stress kinase p-p38 (T180/Y182) among tobacco smokers and monocyte-specific elevated phosphorylation in employees at the explosion site. Other studies of the accident reported reduced tear film stability, and more airway obstruction and subjective health complaints among the employees at the accident site. Elevated monocyte p-p38 in the employee group was independent of such health effects, and could therefore be dependent on the sulphuric malodorous environment. The present study proposes signalling status in leukocytes as a scalable biomarker providing information about environmental exposures.